1f7/2 1d3/2MODEL SPACE AND INELASTIC LONGITUDINAL C6ELECTRON SCATTERING FORM FACTORS IN Ti-50, (RESIDUALINTERACTION CONSIDERATION) - Majeed, Firas; Qassim, Ala'a (Iraqi Journal of Science, 2024)
Skakura Arima Sebe "SAS" has been adopted as an effective interaction togenerate the model space 1f7/2 1d3/2 wave functions with Harmonic oscillator wavefunctions (H.O) as a single particle wave function to study inelastic longitudinal C6electron scattering form factors in Ti-50. The modern realistic M3Y effectivenucleon- nucleon interaction with two sets of fitting parameters (Ried fitting (M3YP1),and Paris fitting (M3Y-P0)) is used. The adjustable interaction "MSDI" hasbeen used as a residual interactions in the calculation of core polarization effectswithin the framework of first order perturbation theory with 2;< excitation energycoupling the core orbits to the higher configurations one across the model space atnormal transition. Theoretical results have been compared with the experimentaldata.PACS:25.30.Dh;21.60.Cs;27.30.+t.